Emotion regulation use in daily-life and its association with success of emotion-regulation, self-efficacy, stress, and state rumination - Int-Veen, Isabell; Volz, Magdalena; Kroczek, Agnes; Fallgatter, Andreas J.; Ehlis, Ann-Christine; Rubel, Julian A.; Rosenbaum, David (Frontiers in Psychology, 2024)
Investigations on emotion regulation strategies (ERS) primarily focus on the influence of instructed emotion regulation (ER) on outcomes. However, recent work has shown that selection of ERS is dependent on e.g. situational demands and personal resources. In this current investigation, we used an online diary to investigate ERS used by free choice and their association with ER-success, stress and rumination. We identified 4 factors of ERS: cognitive perspective change, cognitive-behavioral problem-solving, suppression-distraction and bodysocial ERS. Associations of ERS with stress, state-rumination and ER-success were investigated using multilevel-mixed-models, allowing to separate within-and between-subject effects. Our results show that, on a within-subject level, all adaptive ERS were positively associated with ER-success, while maladaptive ERS as well as higher stress and staterumination were negatively associated with ER-success. On the other hand, only withinsubject cognitive ERS were associated with higher self-efficacy. Maladaptive ERS-use was consequently positively associated with stress and state rumination. Surprisingly, only cognitive perspective change ERS were negatively associated with state rumination.Cognitive-behavioral problem-solving was positively associated with stress and success of emotion regulation. We interpret these results in the light of situational constraints of ERS-use and the importance of the assessment of these in future studies.